Chronic renal failure as a risk fator for heart failure (Research, Society and Development, 2021)
The renal system and the cardiac system are closely connected, in other words, if there’s a change in one of these systems, this alteration directly and/or indirectly influences the functioning of the other. Among the most common changes, related to these two systems, are chronic kidney disease (CKD) and heart failure (HF). CKD is a condition where the kidneys lose their ability to function. HF, on the other hand, is a clinical syndrome characterized by the heart's inability to function properly as a pump, that’s, there’s a modification in both the contraction deficit and it’s relaxation, which is unable to send blood to the rest of the body. This work aims to carry out an integrative literature review to verify the relationship between CKD and HF. For the survey of articles in the literature, a search was carried out in the following databases: Latin American and Caribbean Literature in Health Sciences (LILACS), Medical Literature Analysis and Retrieval Sistem online (Medline), Sicelo, Cochrane and Up to Date. The following descriptors and their combinations in Portuguese, English and Spanish languages were used to search for articles: "Chronic Kidney Failure", "Heart Failure", "Chronic Kidney Disease and Heart Disease" and "Chronic Kidney Disease Related to Heart Disease''. The analysis of studies in the literatute showed that chronic kidney diseade becomes a risk factor for heart failure depending on predisposing factor, such as: iron deficiency anemia, arteriosclerosis, hipertension, previous kidney demage, etc. Thus, this relationship affirms that CKF is a risk factor for HF.